(untitled) (Research, Society and Development, 2021)
Chagas disease, known as American trypanosomiasis, is caused by the protozoan T. cruzi and endemic to Latin America, in which it represents one of the main socioeconomic problems in the region. Transmission routes can be vector, orally, by blood transfusion, organ transplantation, congenital transmission or laboratory accidents. Oral transmission stands out for being one of the main causes of acute Chagas disease (ACD) in some regions. Thus, the work aims to describe the main epidemiological outbreaks of infection with T. cruzi by oral contamination based on the literature and to identify the main sources, places and preventive measures taken in the face of these outbreaks caused by oral contamination. The bibliographic review was carried out in the databases: Latin American and Caribbean Literature in Health Sciences (LILACS), Scientific Electronic Library Online portal (SCIELO) and PubMed. At the end of the selection, 13 articles were used for the development of the study. The studies showed that the main foods associated with acute Chagas infection were sugarcane juice, açaí, açaí juice, contaminated water, palm heart juice and guava juice. The main localities affected were Brazil, Pará, Amapá and Amazonas, and other Latin American countries such as French Guiana and Venezuela. In addition, the studies pointed out sanitary control practices, the cooking process, the adoption of basic structural measures combined with not using artificial lighting as possible measures to reduce the risk of contamination in these areas. Finally, this work brings a survey that favors a better characterization of the importance of oral transmission of Chagas disease in the last 12 years in Latin America.